Facile Chemoenzymatic Strategies for the Synthesis and Utilization of S‐Adenosyl‐L‐Methionine Analogues1. Issue 15 (11th March 2014) - Singh, Shanteri; Zhang, Jianjun; Huber, Tyler D.; Sunkara, Manjula; Hurley, Katherine; Goff, Randal D.; Wang, Guojun; Zhang, Wen; Liu, Chunming; Rohr, Jürgen; Van Lanen, Steven G.; Morris, Andrew J.; et al.
Abstract A chemoenzymatic platform for the synthesis of S‐adenosyl‐L‐methionine (SAM) analogues compatible with downstream SAM‐utilizing enzymes is reported. Forty‐four non‐native S/Se‐alkylated Met analogues were synthesized and applied to probing the substrate specificity of five diverse methionine adenosyltransferases (MATs). Human MAT II was among the most permissive of the MATs analyzed and enabled the chemoenzymatic synthesis of 29 non‐native SAM analogues. As a proof of concept for the feasibility of natural product "alkylrandomization", a small set of differentially‐alkylated indolocarbazole analogues was generated by using a coupled hMAT2–RebM system (RebM is the sugar C4′‐O‐methyltransferase that is involved in rebeccamycin biosynthesis). The ability to couple SAM synthesis and utilization in a single vessel circumvents issues associated with the rapid decomposition of SAM analogues and thereby opens the door for the further interrogation of a wide range of SAM utilizing enzymes.